Improving induction of labour - a quality improvement project addressing Caesarean section rates and length of process in women undergoing induction of labour. Issue 1 (10th September 2015) - O'Dwyer, Sabrina; Raniolo, Caterina; Roper, Janice; Gupta, Manish
Abstract: Induction of labour (IOL) in maternity care is often not an area of priority in maternity services, which often results in protracted delays, a poor patient experience, and patient complaints. Caesarean section (CS) rates among women undergoing IOL at this inner city district general hospital were noted to be higher than other units nationwide. We collected pre and post-intervention data of the following outcome measures: time taken to administer prostaglandin after arrival, time taken to achieve established labour, mode of delivery, and user satisfaction scores. Our introduction of a dedicated IOL Suite, promotion of out-patient IOL, use of a single administration prostaglandin (as opposed to traditional six hourly prostaglandin), widespread staff engagement and rolling audit has resulted in positive change in the maternity unit. CS rates for women undergoing IOL have been reduced from 29% to 22% (p=0.05), time taken to administer the induction medication has decreased from 6.3h to 2.7h (p=0.0001), and out-patient induction rates have increased from 3% to 33% (p=0.001). We have achieved a reduction in the overall length of in-patient stay. We have also received positive feedback from both staff and patients. We used a bottom-up approach, engaging frontline staff in problem identification and pathway design. Our staff engagement questionnaire showed other benefits such as increased staff morale as a result. Collection of simple performance data and sharing of this in real time with staff acts as a valuable tool for acceptance of change and continuous improvement. Communicating plans to a large body of people is important in ensuring the success of an intervention. Staff showing disengagement may require specific detailed information to allay their concerns. Following initial successes, ongoing vigilance, and collection of audit data is key to sustaining any improvement.